2016
DOI: 10.1371/journal.pntd.0004959
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Local Mosquito Species Incriminates Aedes aegypti as the Potential Vector of Zika Virus in Australia

Abstract: BackgroundWithin the last 10 years Zika virus (ZIKV) has caused unprecedented epidemics of human disease in the nations and territories of the western Pacific and South America, and continues to escalate in both endemic and non-endemic regions. We evaluated the vector competence of Australian mosquitoes for ZIKV to assess their potential role in virus transmission.Methodology/Principal FindingsMosquitoes were exposed to infectious blood meals containing the prototype African ZIKV strain. After 14 days incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 38 publications
(47 reference statements)
9
77
1
Order By: Relevance
“…aegypti mosquitoes, with the difference in the percentage of mosquitoes infected and the percentage with infectious saliva broadly consistent with the reported rates for a variety of ZIKV isolates in these mosquitoes (23, 25). Previous studies have shown that Australian A.…”
Section: Discussionsupporting
confidence: 85%
“…aegypti mosquitoes, with the difference in the percentage of mosquitoes infected and the percentage with infectious saliva broadly consistent with the reported rates for a variety of ZIKV isolates in these mosquitoes (23, 25). Previous studies have shown that Australian A.…”
Section: Discussionsupporting
confidence: 85%
“…quinquefasciatus or Cx . pipiens indicate that many geographically distinct populations are refractory to virus transmission [46,47,5154]. These results are similar to our findings in both SPONV strains, where infection and dissemination was not detected in Cx .…”
Section: Discussionsupporting
confidence: 90%
“…These viruses belong to diverse families including the Flaviviridae (genus: Flavivirus ) that are positive single‐stranded RNA viruses (Fauquet, Mayo, Maniloff, Desselberger, & Ball, 2005; Karabatsos, 1978). Flaviviruses include Japanese encephalitis virus and Murray Valley encephalitis virus transmitted by Culex species (Erlanger, Weiss, Keiser, Utzinger, & Wiedenmayer, 2009; Kay, Fanning, & Carley, 1984), West Nile virus (WNV) transmitted by a diverse group of mosquitoes including Aedes and Culex species (Mackenzie et al., 2004) and yellow fever virus (YFV), Zika virus (ZIKV), and dengue virus (DENV) that are all transmitted by Aedes aegypti and Aedes albopictus (Black et al., 2002; Hall‐Mendelin et al., 2016; Hayes, 2009). Dengue fever caused by DENV is a severely debilitating disease with 40% of the world's population at risk of infection and an estimated 300 new infections reported yearly (Bhatt et al., 2013).…”
Section: Introductionmentioning
confidence: 99%